Hang cleans and hang snatches produce similar improvements in female collegiate athletes - Ayers, JL; DeBeliso, M; Sevene, TG; Adams, KJ (Biology of Sport, 2016)
Olympic weightlifting movements and their variations are believed to be among the most effective ways to improve power, strength, and speed in athletes. This study investigated the effects of two Olympic weightlifting variations (hang cleans and hang snatches), on power (vertical jump height), strength (1RM back squat), and speed (40-yard sprint) in female collegiate athletes. 23 NCAA Division I female athletes were randomly assigned to either a hang clean group or hang snatch group. Athletes participated in two workout sessions a week for six weeks, performing either hang cleans or hang snatches for five sets of three repetitions with a load of 80-85% 1RM, concurrent with their existing, season-specific, resistance training program. Vertical jump height, 1RM back squat, and 40-yard sprint all had a significant, positive improvement from pre-training to post-training in both groups (p≤0.01). However, when comparing the gain scores between groups, there was no significant difference between the hang clean and hang snatch groups for any of the three dependent variables (i.e., vertical jump height, p=0.46; 1RM back squat, p=0.20; and 40-yard sprint, p=0.46). Short-term training emphasizing hang cleans or hang snatches produced similar improvements in power, strength, and speed in female collegiate athletes. This provides strength and conditioning professionals with two viable programmatic options in athletic-based exercises to improve power, strength, and speed.